RUSSIA'S SOFT POWER IN DEMOCRATIC COUNTRIES IN THE WAR WITH UKRAINE (Вісник: Міжнародні відносини, 2024)
"Soft power" is a necessary component of the foreign policy of many countries. russia is openly trying to undermine the Western world’s sentiment, aiming to split the society by manipulating their values. russia's soft power, including its so-called traditional values which attract a large part of far-right parties, as well as messianism, provide russia and its sympathetic allies with channels to legitimize kremlin's actions. By succumbing to these influences, the EU and its allies may inadvertently play into putin's hands and lose in the joint war.
Keywords: soft power, hard power, Ukraine, the West, propaganda, hybridization, manipulation, russian aggression against Ukraine, far-right parties, disinformation campaigns